A global approach to mapping the environmental risk of harbours on aquatic systems. (September 2020) - Valdor, Paloma F.; Gómez, Aina G.; Steinberg, Peter; Tanner, Edwina; Knights, Antony M.; Seitz, Rochelle D.; Airoldi, Laura; Firth, Louise B.; Arvanitidis, Christos; Ponti, Massimo; Chatzinikolaou, Eva; Brooks, Paul R.; et al.
Abstract: The goal of this paper is to propose a screening method for assessing the environmental risk to aquatic systems in harbours worldwide. A semi-quantitative method is based on environmental pressures, environmental conditions and societal response. The method is flexible enough to be applied to 15 harbours globally distributed through a multinational test using standardised and homogenised open data that can be obtained for any port worldwide. The method emerges as a useful approach towards the foundation of a global environmental risk atlas of harbours that should guide the harbour sector to develop a more globally informed strategy of sustainable development. Graphical abstract: Image 1 Highlights: A method is proposed to assess the environmental risk of harbours on aquatic systems. The method is a tool to identify the factors of risk on harbour aquatic systems. Results obtained from 15 globally distributed harbours are analysed. Towards the creation of a global atlas of environmental risk of harbours on aquatic systems.